Fish Tank Granuloma Presenting as a Nasal Cavity Mass. (12th January 2021) - Sekine, Motoki; Goto, Fumiyuki; Saito, Kosuke; Kaneda, Shoji; Yamamoto, Hikaru; Murakami, Tomoaki; Hamano, Takahide; Okami, Kenji
Abstract : Mycobacterium marinum is a free-living nontuberculous mycobacterium that is widely distributed in freshwater and seawater around the world. Granulomatous skin infection from M. marinum in people who are exposed to fish or aquatic environments is a rare condition known as fish tank granuloma. The granuloma mainly occurs on the skin of the upper limb, in a few cases on the face, and rarely in the nasal cavity. We describe a case of M. marinum infection that presented as a nasal cavity mass. A 57-year-old woman who was receiving infliximab for psoriatic arthritis visited our hospital with a complaint of right nasal obstruction. A granulomatous mass with an irregular surface was found in the anterior part of the right nasal cavity. Tissue biopsy revealed granulation tissue. Since the application of steroid ointment did not reduce the size of the mass, the tumor was resected under local anesthesia, and the base was cauterized. The pathological finding was an inflammatory granuloma with negative Ziehl–Neelsen staining. The granuloma recurred 3 months after resection. The interferon-gamma release assay (IGRA) test was positive, and therefore, a mycobacterial tissue culture test was performed because of suspected nasal tuberculosis, which identified M. marinum . The nasal cavity mass disappeared 2 months after the administration of minocycline, followed by clarithromycin, and subsequent discontinuation of infliximab. M. marinum infection can cause an intranasal mass. IGRA and the mycobacterial tissue culture test are useful for diagnosis. As in this case, the nasal lesion may be excised as an inflammatory nasal granuloma, and therefore, there may be many more "hidden" cases of M. marinum infection. If nasal granulation is present, the possibility of M. marinum infection should be considered.